Lipases: An overview of its current challenges and prospectives in the revolution of biocatalysis. (July 2016) - Angajala, Gangadhara; Pavan, Pasupala; Subashini, Radhakrishnan
Abstract: Over the past few years most of the biochemical industries are in a rapid stage of development. The major root cause responsible for this current state of excitement is a new technology-driven biocatalysis that pulled markets in to the new areas. The development of technology from scientific breakthroughs to the industrial applications is rapidly increasing all over the world. The substantial growth and increased emphasis on the development of biocatalysts is an huge achievement both for chemical and biotechnology related industries. In this present world 'chemical biotechnology' is rapidly growing hand-in-hand with maximum utilization of renewable feed stocks and made a big impact in the industrial revolution. The present review mainly summarizes a complete overview of lipases and its biocatalytic applications in pharmaceutical industries especially in the synthesis of (-)-Peroxetine hydrochloride, diltiazem hydrochloride, chiral β-azidoalcohols, primary amines and amides, vitamin D3 derivatives. The catalytic role of lipases in the epoxidation of unsaturated carboxylic acids, in the kinetic resolution of azirinol, aminolysis of dimethyl 3-substituted glutarates in addition to these lipase assisted synthesis of dihydropyrano [2, 3- c ] pyrazoles and 4-methoxy cinnamoyl glycerol was elaborated.